Hubungan Usia Dengan Estrogen Receptor Pada Penderita Kanker Payudara di RSUD Dr. Pirngadi Medan Tahun 2018 - Jumikha Tamara Sahmaulyana Sidauruk (Universitas HKBP Nommensen, 2020)
Background: Breast cancer is a malignancy in breast tissue that can be originated from ductal epithelium and lobules. It is the main cause of death from cancer suffered by women in the world. Age and hormonal are important risk factors for breast cancer where the longer a person is exposed to estrogen, the higher is the risk for breast cancer. The estrogen receptor is one of the main prognostic and predictive factors examined in breast cancer and can be determinant for hormonal therapy. Objectives: This study aimed to discover the relation between age and estrogen receptor in breast cancer patients of RSUD Dr.Pirngadi Medan in 2018. Methods: This research was an analytical study with a cross-sectional design. The research sample was 96 breast cancer patients by medical records of RSUD Dr.Pirngadi Medan in 2018 collected by a consecutive sampling method. Analysis of the data in this study was done by univariate to describe the characteristics of research subjects, while bivariate analysis used the chi-square test method to analyze the relationship between age and estrogen receptor. Results: The patients with breast cancer in RSUD Dr.Pirngadi Medan 2018 was mostly >40 years old (79.2%), with negative estrogen receptor hormonal status (53%), status was married (99%), and the highest level of education was high school (54.2%). The results of the study showed that there was a relationship between age and estrogen receptor in breast cancer patients with p-value =0.007 (p value<0,05). Conclusion: There was a significant relationship between age and estrogen receptors and estrogen receptors in breast cancer patients in RSUD Dr.Pirngadi Medan 2018.